Effects of a Visual Distracter Task on the Gait of Elderly versus Young Persons. (17th May 2011) - Bock, Otmar; Beurskens, Rainer
Abstract : Seniors show deficits of dual-task walking when the second task has high visual-processing requirements. Here, we evaluate whether similar deficits emerge when the second task is discrete rather than continuous, as is often the case in everyday life. Subjects walked in a hallway, while foot proprioception was either perturbed by vibration or unperturbed. At unpredictable intervals, they were prompted to turn their head and perform a mental-rotation task. We found that locomotion of young subjects was not affected by this distracter task with or without vibration. In contrast, seniors moved their legs after the distraction at a slower pace through smaller angles and with a higher spatiotemporal variability; the magnitude of these changes was vibration independent. We conclude that the visual distracter task degraded the gait of elderly subjects but completely spared young ones, that this effect is not due to degraded proprioception, and that it rather might reflect the known decline of executive functions in the elderly.